THE NURSE'S WORK PROCESS IN BASIC CARE: MANAGEMENT AND ASSISTANCE: THE NURSE'S WORK PROCESS IN BASIC CARE: MANAGEMENT AND ASSISTANCE - Feitosa, Ankilma do Nascimento Andrade; Santos, Rita De Cássia Pereira; Alencar Neta, Raimunda Leite de; Silva, Talina Carla da; Silva, Macerlane de Lira; Dantas, Joanny Laissa Pinheiro (Brazilian Journal of Production Engineering, 2020)
The study aimed to analyze the work process of nurses in Primary Care, relating the dimensions of management and care. The research was constituted through an integrative literature review, which are, problematization and identification of the outline, literary or database research, categorization of the theme, evaluation of the selected studies, interpretation of the segments, and the demonstration of the integrative review. According to the literature found, it was possible to establish two thematic categories: (I) Contributions of the nurse's work process in Primary Care and (II) Evaluation of management and nursing care in primary care. However, it was possible to identify that nursing care is fundamental for resolving health actions, and management practices contribute to the effective access and promotion of the population's health, where it is emphasized that nurses consolidate their managerial actions and assistance in a positive way for the population in different contexts.
Keywords: Comprehensive Health Care; Primary Health Care; Public Health